Constipation: A Physiological Approach - W Grant Thompson (Canadian Journal of Gastroenterology)
The first step in managing a patient with constipation is to understand the precise nature of the complaint. Is the onset recent? What are the frequency and form of the stools, and how much effort is required to defecate? Is constipation steady or alternating as in irritable bowel syndrome? Are there structural, metabolic or pharmacological confounders? Is the patient depressed? Has dietary fibre been tried at a sufficient dose? What are the patient’s understanding and beliefs about the symptoms? Has there been sufficient and appropriate investigation? Armed with the answers to these questions, physicians can help most patients through lifestyle, dietary and pharmacological adjustments, along with supplementary fibre. Some patients may require regular doses of an osmotic laxative. Those few that fail these measures should have their transit time estimated while on a high fibre diet; if it is normal, further testing is unlikely to help. The above efforts should be re-emphasized, and reassurance should be offered. Some patients may require a psychological assessment. If transit time is prolonged and the patient may benefit from surgery for colonic inertia or biofeedback for anismus, then colon and anorectal function should be assessed. The decision to perform further tests should be made carefully, and unrealistic expectations should be discouraged. Before surgery is offered, the patient should have the benefit of receiving an expert opinion. Biofeedback helps some patients with isolated anorectal dysfunction.